Senior High School Background and GPA of the Education Students in a State University in the Philippines - et. al., Marvin S. Canque, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study investigated the Senior High school Background and the GPA of Education students in a State University in the Philippines. The study utilized the Descriptive Correlational method. The study respondents are the one hundred sixty-three incoming third-year education students with a specialization in Mathematics, Home Economics, and General education. Moreover, the study revealed that high school academic achievement is the most common significant variable that positively impacts their college GPA among the three groups of education students. In addition, the study found a negative association between the GPA of education students major in mathematics and their Senior High School Strand. It is concluded that senior high school academic achievement is still the best indicator of college GPA. It is recommended that the college/department admission policy emphasize and give more consideration to the student’s prior academic performance except for passing the university/department entrance examination.